Rialological properties of modified mineral additions dentifrices added to cement concrete - Marozova, Nina Niklievna; Qais, Hamza Abdul Malik (Arab Journal for Sciences and Research Publishing, 2016)
This study deals with the geological properties of silica and silicate dust, where water quantity and mobility were determined. The study also examined the effect of water-reduced plasticizers on silica and silicate dust. Five types of polycarbonate , and five kinds of mineral additives were studied in this research. This study deals with the geological properties of silica and silicate dust, where water quantity and mobility were determined. The study also examined the effect of water-reduced plasticizers on silica and silicate dust. Five types of polycarbonate , And five kinds of mineral additives. The results showed that the mineral additives used in the concrete mix were affected by varying degrees when adding the chemical parameters to their potions and the ability of these chemical additives to reduce the water quantity in these pastes has been tested. The research showed that there is a strong relationship between the geological properties and the surface of the mineral, the larger the surface area the greater the amount of water required flow units, and the compatibility of plasticizers with mineral additives depends mainly on the structural structure of the metal.